What is inside THIS box? - Daywalt, Drew (Daywalt, Drew. Monkey & Cake book., 2019)
"Monkey has a big box, which he tells Cake has a cat inside, but only when the box is closed; Cake suggest that maybe it is a dinosaur instead, and the two friends puzzle over how they can solve the problem of finding out what is in the box, if it is always empty when opened." --